Implementation of Project Based Learning Assisted by PhET Simulation in Science Learning to Improve Students' Science and Digital Literacy - Wijayanti, Arfilia; Fajriyah, Khusnul; Azizah, Mira; Kiswoyo, Kiswoyo (Journal of Innovative Science Education, 2025)
Mastering scientific and digital literacy is essential for prospective teachers to meet the demands of modern science education. This study specifically aims to analyze the effectiveness of Project-Based Learning (PjBL) assisted by PhET simulations in improving students’ scientific and digital literacy. A quasi-experimental design with a pretest–posttest control group was conducted involving 80 undergraduate students, and the data were analyzed using N-Gain and comparative statistical tests. The results show that the implementation of PjBL supported by PhET simulations significantly outperformed conventional learning, with the experimental group achieving a higher N-Gain across all indicators of scientific and digital literacy. These improvements were also reflected in students’ project performance, demonstrating stronger conceptual understanding and more proficient use of digital tools during inquiry-based activities. These findings highlight the potential of integrating interactive simulations within PjBL to strengthen essential competencies in teacher education programs and support the development of innovative science learning practices aligned with 21st-century educational demands.